Stochastic Resonance Whole-Body Vibration, Musculoskeletal Symptoms, and Body Balance: A Worksite Training Study - Achim Elfering; Sibille Arnold; Volker Schade; Christian Burger; Lorenz Radlinger (Elsevier, 2013)
Background: Stochastic resonance whole-body vibration training (SR-WBV) was tested to reduce work-related musculoskeletal complaints. Methods: Participants were 54 white-collar employees of a Swiss organization. The controlled crossover design comprised two groups each given 4 weeks of exercise and no training during a second 4-week period. Outcome was daily musculoskeletal well-being, musculoskeletal pain, and surefootedness. In addition, participants performed a behavioral test on body balance prior to when SR-WBV started and after 4 weeks of SR-WBV. Results: Across the 4-week training period, musculoskeletal well-being and surefootedness were significantly increased (p < 0.05), whereas musculoskeletal pain was significantly reduced only in those who reported low back pain during the last 4 weeks prior to the study (p < 0.05). Body balance was significantly increased by SR-WBV (p < 0.05). Conclusion: SR-WBV seems to be an efficient option in primary prevention of musculoskeletal complaints and falls at work.